2018
DOI: 10.1166/jnn.2018.15393
|View full text |Cite
|
Sign up to set email alerts
|

Highly Transparent Poly(vinyl alcohol)(PVA)/TiO2 Nanocomposite Films with Remarkable Photocatalytic Performance and Recyclability

Abstract: Titanium dioxide (TiO2) has been regarded as an efficient photocatalyst for degradation of environmental pollutants. However, recovery of TiO2 nanoparticles from suspension limits its practical application. Herein, we reported a novel highly transparent poly(vinyl alcohol)(PVA)/TiO2 photocatalytic film via in-situ growth and solution casting method. TiO2 nanoparticles with average size of 10 nm were uniformly dispersed in transparent PVA matrix. The photocatalytic performance was investigated by photodegradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Additionally, the swelling ability of crosslinked PVA obtained by chemical or physical crosslinking methods can ensure that the embedded photocatalyst nanoparticles are fully in contact with the pollutants [60]. In addition, (i) Lei et al [60] and Ghule et al [65] verified that the treated catalyst/PVA matrix exhibited higher efficiency than the untreated matrix, because the untreated one displayed many catalyst aggregates and a non-homogeneous dispersion; (ii) Yan et al [47] and Yan et al [48] found that the heat treatment yields a transparent film; (iii) Yan et al [47] and Song et al [79] found that treating the PVA extends the light absorption of TiO 2 to the visible light region, as far as 800 nm; (iv) Yan et al [47], Wang et al [54], and Ren et al [68] reported that heat treatment improves the stability of the materials, which could be reused 5-8 times without efficiency loss. Furthermore, Lei et al [60] reused the materials for 25 cycles without a loss of efficiency.…”
Section: Pva-supported Photocatalysismentioning
confidence: 98%
See 2 more Smart Citations
“…Additionally, the swelling ability of crosslinked PVA obtained by chemical or physical crosslinking methods can ensure that the embedded photocatalyst nanoparticles are fully in contact with the pollutants [60]. In addition, (i) Lei et al [60] and Ghule et al [65] verified that the treated catalyst/PVA matrix exhibited higher efficiency than the untreated matrix, because the untreated one displayed many catalyst aggregates and a non-homogeneous dispersion; (ii) Yan et al [47] and Yan et al [48] found that the heat treatment yields a transparent film; (iii) Yan et al [47] and Song et al [79] found that treating the PVA extends the light absorption of TiO 2 to the visible light region, as far as 800 nm; (iv) Yan et al [47], Wang et al [54], and Ren et al [68] reported that heat treatment improves the stability of the materials, which could be reused 5-8 times without efficiency loss. Furthermore, Lei et al [60] reused the materials for 25 cycles without a loss of efficiency.…”
Section: Pva-supported Photocatalysismentioning
confidence: 98%
“…In this process, the dispersion of nanoparticles in the polymer matrix is a critical issue in the successful preparation of transparent hybrid nanocomposites; therefore, after mixing, sonication methods are applied to disperse the particles [46]. The hydrothermal process is similar, because it involves mixing of the polymer and the catalyst, but it is performed at high temperatures [47,48].…”
Section: Polymer Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers reported that some of the nanofiller doped PVA composites, and biopolymer blend PVA showed efficient removal of MB dye [29][30][31][32]. researchers also have reported that nanofiller and biomolecule doped PVA composites show excellent optical properties [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating some nano-sized fillers can improve the composite properties required for many industrial and technological applications. Polymer nanocomposite films with inorganic fillers can improve stiffness, strength, hardness, and high temperature creep resistance compared to unfilled polymers [ 1 , 2 , 3 ]. These nanocomposite films have recently become an issue of great concern from an economic, environmental, and performance point of view.…”
Section: Introductionmentioning
confidence: 99%